Screening of Oat Accessions for Fusarium Head Blight Resistance Using Spawn‐Inoculated Field Experiments. Issue 1 (1st January 2018) - Tekle, Selamawit; Lillemo, Morten; Skinnes, Helge; Reitan, Lars; Buraas, Trond; Bjørnstad, Åsmund
ABSTRACT: Use of resistant cultivars is one of the most important measures to reduce the risk of Fusarium head blight (FHB, caused by various Fusarium spp.) and mycotoxins in cereals. Research on resistance to FHB has mainly focused on wheat ( Triticum aestivum L.) and barley ( Hordeum vulgare L.) and is very limited in oat ( Avena sativa L.). In Norway, routine testing of cultivars and breeding lines has been performed in spawn‐inoculated field experiments with Fusarium graminearum Schwabe as part of a concerted research and breeding effort to improve FHB resistance in oat. Data on FHB symptom, days to flowering, and plant height have been collected during the field seasons. Together with the field data, deoxynivalenol (DON) content and germination capacity of harvested kernels are used to score resistance levels of genotypes. In this paper, results are presented from a combined analysis of data from 9 yr of field trials from 2008 to 2016. Consistent and highly significant differences in DON content and germination capacity were documented among the current oat cultivars on the Norwegian market. These two negatively correlated parameters are used as selection criteria in breeding since they are relevant for the different end uses of the grains: DON content for use as food and feed, and germination capacity for seed production. In the paper, we discuss the pros and cons of the various screening methods and parameters used in assessing FHB resistance in oat and present the progress made in resistance breeding based on an established field testing methodology.